A Diagnostic Investigation of Explosive Maritime Cyclogenesis during FGGE. - Smith,Darrell H (1986)
A collection of explosive and non-explosive storm groups are selected from the western North Atlantic Ocean and western North Pacific Ocean. Explosive cyclogenesis is defined as having a mean sea level pressure fall of 1 mb h for 24 h. Using ECMWF(European Center for Medium Range Forecasts) analyses with FGGE SOP-1 data, the storm environment properties of both storm types are analyzed and compared. Storm environment properties include static stability, layer averaged potential temperature, low level vorticity, vorticity advection, mean and eddy modes of vorticity transport, divergence and kinematic vertical velocities. These properties are compared between the cyclones types at 0 h, 12 h and 24 h periods as well as the overall 24 h average. The largest differences between the explosive group and the non-explosive group are found in the upper level divergence and vorticity advection. The explosive systems are warmer; however, static stabilities of the two groups are quite similar. Keywords: Explosive cyclogenesis; Vorticity advection; Mass divergence; Static stability; Potential temperature; Absolute vorticity; Theses.